Capability of some planted mangrove types to decrease the height of wave breaking the seashore at the Hai Phong littoral - Thai, Vu Doan; Tuan, Mai Sy (Academia Journal of Biology, 2014)
After studying and measuring the structure of some artificial mangrove types at the Haiphong littoral, so as the trang (Kandelia obovata Sheue, Liu & Yong) and the ban (Sonneratia caseolaris (L.) Engl.) types, using the wave frequency gauge DNW-5M, IVANOP H-10 and mia at the Bangla village, Doson hamlet, we are ascertaining that the structure, the density, the size, the broadness of the planted area and the ancienty of the plantation have significant influence on the decrease of the wave height by increasing the decrease coefficient of the wave height on the direction from the sea into the land through the mangrove (on condition that the trees of the mangrove not been submerged up at hight tide). Notably, at Bangla, the average wave height on East-South direction, in front of the trang plantation, is 0.48 m but through 650 m of the planted mangrove broadness, it falls down to 0.03 m, i.e. the decrease coefficient is reaching 93 percent. In the meantime at Vinhquang village (Tienlang district), the average wave height on the East-South direction at 100 m far from the ban mangrove with 920 m broadness is 0.54 m then falls down to 0.05 m after overcoming through such mangrove i.e. the decrease coefficient of the wave height is 90 percent. On the nude area without any planted mangrove, the derease coefficient is comparatively 37 percent only.